More than opinion expression: Secondary effects of intraparty referendums on party members. (November 2019) - Wuttke, Alexander; Jungherr, Andreas; Schoen, Harald
As political parties expand opportunities for intraparty participation, understanding the effects of participatory events on party actors becomes ever more important. In this study, we investigate the consequences of an intraparty referendum in a state branch of Germany's Christian Democratic Union on beliefs and attitudes of party members. We use longitudinal survey data bracketing a nonbinding issue referendum on the party's stance on same-sex marriage. Our analysis shows that the referendum had secondary effects that went beyond the referendum's primary goal of delivering an informal opinion poll to the party leadership. The experience of having a say in an important policy decision fostered members' sense of party-specific efficacy. Furthermore, the referendum provided party members with information on elite positions and stimulated leadership evaluation based on issue congruency. Altogether, involvement in intraparty decision-making promotes beliefs and behaviours among the rank and file that are relevant to uphold a vivid and empowering party life.